Pengaruh Current Ratio, Debt to Equity Ratio dan Firm Size terhadap Return on Equity - Jufrizen Jufrizen; Maya Sari (Jurnal Riset Akuntansi, 2019)
The purpose of this study is to analyze whether variables such as Current Ratio, Debt to Equity Ratio and Company Size have a partial or simultaneous influence on Return On Equity. The approach taken in this study is an associative approach. The population in this study were all Agriculture Subsector Companies listed on the Indonesia Stock Exchange (IDX) which numbered 14 companies, while the samples that met the criteria in sampling for this study were 6 Agricultural Subsector Companies listed on the Indonesia Stock Exchange (IDX). Analysis of sample data used in this study is Multiple Linear Regression. The results of the study show that partially Current Ratio has no significant effect on Return On Equity, Debt to Equity Ratio has no significant effect on Return On Equity and Firm Size does not have a significant effect on Return On Equity. Simultaneous Results show that Current Ratio, Debt to Equity Ratio and Company Size have no significant effect on Return On Equity.